Determinação de disruptores endócrinos em filé de peixe utilizando QuEChERS modificado e GC-(TQ)MS/MS - Munaretto, Juliana Scariot (2012)
Endocrine Disrupter Compounds (EDCs) like pesticides, alkylphenols and hormones among other classes of compounds are responsible for alterations in the endocrine system functions. Endocrine disruption occurs when EDCs interact with the hormone receptors, altering the natural response patterns of the endocrine system. Aquatic organisms, such as fish, are able to accumulate EDCs residues in concentration several times higher than the surrounding water. Consequently, fish is a major source of contamination for both top predators and human consumers. This study aimed to develop and validate a fast method for the determination of 40 endocrine disrupters in fish fillet, using modified QuEChERS and Gas Chromatography coupled with Mass Spectrometry in tandem, using a triple quadrupole analyzer (GC-(TQ)MS/MS). A factorial design was performed to optimize the extraction procedure, which consist of the extraction of 10.0 g of fish fillet with 10.0 mL of acetonitrile with 1% (v/v) of acetic acid followed by manual shaking for 1 min. In the partition step 2.0 g of sodium chloride, 1.7 g of anhydrous sodium acetate and 0.3 g of anhydrous magnesium sulfate were added, followed by shaking and centrifugation at 3400 rpm for 8 min. Then the extract was transferred to a 15 mL polypropylene tube containing the C18 and PSA sorbents, beyond the anhydrous magnesium sulfate. After shaking and centrifuging, the supernatant was filtered and analyzed by GC-(TQ)MS/MS. The method was validated by spiking the blank sample at three concentration levels (10, 25 and 50 Ug kg-1) obtaining recovery values between 70.1 to 120.0% for 36 of the 40 endocrine disrupters evaluated. RSD values below 20% ensured the good precision of the method. The linearity was evaluated using the coefficient of determination (r2) with values higher than 0.996 for all compounds. The matrix effect was evaluated, and it was pretty intense for most compounds, with values exceeding 10%. This effect was compensated using analytical curves obtained with standards prepared in blank matrix extracts. This method was applied in 6 samples of fish fillet from different species. Residues of bisphenol A, chlorpyrifos and bifenthrin were detected. Therefore, the modified QuEChERS method proved to be appropriated for the determination of endocrine disrupters in fish fillet using GC-(TQ)MS/MS since it showed to be effective and can be applied to routine analysis.